1996
DOI: 10.1017/s0021859600078011
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of digestion in cattle fed sugarcane: model development

Abstract: A dynamic model of digestion and absorption of nutrients in cattle fed sugarcane-based diets is described. There are 11 rumen state variables, and four zero pools representing absorbed nutrients. The rumen state variables represent nitrogen, carbohydrate, long chain fatty acid, microbial and volatile fatty acid pools. The zero pools relate to absorbed amino acids, glucose, long chain fatty acids, and volatile fatty acids. The flux equations are described by mass-action and Michaelis-Menten forms. Wherever poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 41 publications
0
21
0
1
Order By: Relevance
“…This follows from the original axiom of Blaxter et al (1956), who argued that whole tract digestibility or the extent of rumen degradation is a constant estimated from the kinetics parameters for passage and degradation, which forms the basis for models describing the extent of rumen degradation (Dijkstra et al, 1996;AFRC, 1998;France et al, 2000). Both enriched silages (GSH and GSL) showed a decrease in d 13 C in the DM and NDF fractions in the residue after in vitro fermentation up to 24 h, after which time the level of enrichment showed no further decline (Figure 2).…”
mentioning
confidence: 99%
“…This follows from the original axiom of Blaxter et al (1956), who argued that whole tract digestibility or the extent of rumen degradation is a constant estimated from the kinetics parameters for passage and degradation, which forms the basis for models describing the extent of rumen degradation (Dijkstra et al, 1996;AFRC, 1998;France et al, 2000). Both enriched silages (GSH and GSL) showed a decrease in d 13 C in the DM and NDF fractions in the residue after in vitro fermentation up to 24 h, after which time the level of enrichment showed no further decline (Figure 2).…”
mentioning
confidence: 99%
“…The inclusion of the new features in the model developed by Dijkstra et al (1996a) was accomplished at the Animal Science Department of the Wageningen University. The model was run using the simulation program SMART ® developed at this university.…”
Section: Methodsmentioning
confidence: 99%
“…Fatty acid fractions include long chain fatty acids (Ld) and volatile fatty acids (Va) and, the rumen microbial DM (Mi) is represented by one state variable. Detailed description of the model and applications are described in Dijkstra et al (1996a;1996b).…”
Section: Model Modificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Litwińczuk et al (2013), a wider range of fodders, i.e., haylage in addition to maize silage, could contribute to higher efficiency of nutrient absorption and, consequently, to higher daily gains in young bulls. Grosse et al (1991;Dijkstra et al, 1996), observed a correlation between higher efficiency of nutrient utilization and higher body weight gains in cattle. Litwińczuk et al (2012), demonstrated that the body measurements of bulls were affected by both cattle breed and feeding intensity.…”
Section: ±08 Explanatory Notes As Inmentioning
confidence: 98%